Energy-saving technology for processing of exhausted etching solutions with obtaining of ferromagnetic compounds - Samchenko, Dmitry N.; Kochetov, Gennadii М.; Vasiliev, Aleksey; Derecha, Dmitry A.; Skirta, Yurii B.; Lastivka, Oles V. (Kyiv National University of Construction and Architecture, 2022)
Exhausted etching solutions are the waste of industrial enterprises and contain toxic pollutants that have a detrimental effect on the environment. Currently, the processing of these solutions to obtain marketable products is important. The paper presents the results of research on the application of the ferritization method for processing of exhausted etching solutions of steel surfaces. Energy-saving activation of the process by alternating magnetic fields was used, which has undeniable advantages compared to traditional thermal activation. The influence of the initial concentration of iron ions in the reaction mixture of ferritization process and the methods of its activation on the treatment quality of exhausted etching solutions was studied. It was established that the best degree of extraction of heavy metal ions from exhausted etching solutions by ferritization is achieved when the reaction mixture is activated by alternating magnetic fields at an initial concentration of iron ions of 6.6 g/dm3 . At the same time, the residual concentration of iron ions in purified solutions does not exceed 0.03 mg/dm3 , that corresponds to degree of purification of solutions of 99.999%. Those solutions can be reused in situ. The qualitative and quantitative composition of ferritization sediments was studied. Phases of ferroxygite δ-FeOОН, magnetite Fe3O4 and maghemite ɣ-Fe2O3 were detected by X-ray phase analysis in the sediments. It was established that at the initial concentration of iron ions of 26.6 g/dm3 with thermal activation of the reaction mixture and 16.6 g/dm3 with alternating magnetic fields activation, the sediment exclusively contains the magnetite phase. The results of the study indicate the possibility of further use of sediments for the production of important industrial products and materials containing ferromagnetic compounds. The implamitation of improved ferritization process in industrial enterprises will allow to achieve decrease of energy consumption compared to known technologies of exhausted etching solutions processing.